Antibiofilm activity of flavonoid mangosteen pericarp extract against porphyromonas gingivalis bacteria - Aprillia Sonya Federika; Mandojo Rukmo; Setyabudi Setyabudi (Conservative Dentistry Journal, 2020)
Background. Necrosis teeth need a procedure called the root canal treatment to eliminate microorganisms in root canal, so the inflammation process did not continue to the periapical.One of the microbes that exist in thenecrosis teethis Porphyromonas gingivalis, that capable of forming biofilm because it has the ability to communicate with bacteria signaling (quorum sensing). It is necessary to discover another antibiofilm agent as an irrigation material in root canal preparation deriving from nature. Flavonoidmangosteen pericarp extract can disrupt acyl-homoserine lactones (AHLs) thus quorum sensing bacteria will be disrupted and causing permanent attachment and the establishment of colonies on the surface of the teeth any barrier. Purpose. The aim of this study found out the antibiofilmactivity of flavonoid mangosteen pericarp extract against Porphyromonas gingivalis bacteria. Method. This studyhasa laboratory experimental with post-test only group design. Porphyromonas gingivalis ATCC 33277 was diluted according to Mc. Farland standard 106CFU/ml in Tryptic Soy Broth (TSB) medium and inserted into microtitterplate flexible U bottom. Porphyromonas gingivalis was incubatedfor 6x24 hour and checked with a simple staining to see the formation of biofilm. Flavonoid mangosteen pericarp extract was added in various concentrations and OD (optical density) readings done with a wavelength of 595 nm. Result. Flavonoid mangosteen pericarp extractshowed a decrease of OD value from control in all concentrations.Conclusion.Flavonoid mangosteen pericarp extract has antibiofilm activity against Porphyromonas gingivalis bacteria.